KRITERIA MEMILIH PASANGAN IDEAL DI ERA DIGITAL: PERSPEKTIF GEN Z - Chaliza, Olifa; Oktaviani, Witia (USRAH: Jurnal Hukum Keluarga Islam, 2025)
The digital era builds cross-cultural relationships, so there is a shift in choosing the ideal partner criteria. According to the Muslim community, this is a highlight in itself, Islam has long regulated the concept of choosing a partner by making religion the main foundation. The purpose of this study is to examine the extent to which the digital era influences the views of generation Z in choosing the ideal partner, knowing the criteria for couples who are considered ideal, and examining these preferences through a normative perspective sourced from Islamic law, Marriage Law, and sharia maqashid. This study uses a qualitative approach with field studies through interviews and open questionnaires, involving Muslim university students spread across Java, Kalimantan, and Medina as purposive subjects. The results of this study show that Gen Z who live in the digital era is influenced by various platforms and information accessed. The criteria for choosing the ideal partner based on the perspective of Gen Z in the digital era are; apply Islamic teachings in daily life, have a vision and mission that is in line with and be responsible, established, physically attractive, sekufu and able to establish healthy relationships. Gen Z not only prioritizes religious aspects, but also considers social factors, which reflects a shift from traditional norms. The results of the normative analysis indicate that despite the change in preferences, these criteria are still in line with religious teachings and national law. This study contributes in the form of fostering responsive Muslim families in the digital era.